Estrogenic Endocrine Disruptors and their Possible Deleterious Effects on Marine Organisms: Use of a Novel Monitoring Bioassay - Hamza-Chaffai, Amel (International Journal of Biotechnology for Wellness Industries, 2013)
Estrogens are both natural and synthetic substances that mimic the effect of the female estrogenic hormone in the body and impart estrogenic activity. Human wastes, birth control pills and chemicals like detergents are a major source of estrogens in the environment. In waste water treatment plants, a major part of these estrogens are not removed after treatment and are released in the marine environment. They are suspected to interfere with the exposed aquatic species’ endocrine systems. In fact, they mimic the effect of the endogenous hormone and therefore can disrupt the endocrine systems of exposed species and the reproductive systems of aquatic fauna. To understand their environmental fate, the estrogenic activity was studied by using the Yeast Estrogenic Screening (YES) bioassay. This bioassay has been validated in the detection of a wide range of estrogenic receptor agonists. A reverse phase HPLC method was used to identify the nature of estrogenic components.We focused on two marine bivalves Ruditapes decussatus and Cerastoderma glaucum recognised bioindicator organisms useful in biomonitoring. Our work is based on in situ and in vivo studies. Different compartments were used: the effluents of a wastewater treatment plant, the sea water, the sediment and the clam Ruditapes decussatus. Some observed histological effects showing hermaphroditic cases and parasites in the cockle Cerastoderma glaucum are also discussed in this paper.